Peningkatan hasil belajar matematika siswa dengan menerapkan model pembelajaran project-based learning melalui lesson study - Nopyta Intan Sari; Saiful Rahman; Shahibul Ahyan (Journal of Didactic Mathematics, 2023)
The learning outcomes of students who are under the minimum completeness criteria (KKM) in mathematics. One of the factors that can affect learning outcomes is the learning model used. The purpose of this study is to apply to improve student learning outcomes by a project-based learning model with the window shopping method through lesson study. The research method used is classroom action research through lesson study with quantitative descriptive data analysis. The data collection in this study used test instruments in the form of multiple choices and descriptions. The results of the study show that by applying the project-based learning model, student learning outcomes increase, as can be seen from the changes in the mastery of classical learning from 14.7% to 79.41%.